Dorsal Metacarpal Artery Perforator Flap for Skin Ulcer Due to a Postoperative Complication of Suture Anchor Treatment for Tendinous Mallet Finger. (5th October 2020) - Yano, Koichi; Kaneshiro, Yasunori; Sasaki, Ryo; Hyun, Seungho; Sakanaka, Hideki
The suture anchor method of surgery has some complications. To best of our knowledge, no report on skin ulcer formation apart from the surgical site after tendinous mallet finger injury using suture anchor is available. We present the case of a 73-year-old woman who sustained tendinous mallet finger in an accident. She was treated surgically with a suture anchor. At 12 months after surgery, the string from the surgical site was removed; 28 months after surgery, a skin ulcer was formed 2-cm proximal from the operative scar, and discharge leaked from the dorsal middle phalanx. Because the wound could not heal by conservative treatment, it was treated surgically. At initial surgery, debridement of the skin ulcer, including the suture knot, was performed. At second surgery, the skin defect was reconstructed using a third dorsal metacarpal artery perforator flap. At 1 year postoperatively, she had no symptoms without recurrence.